The effect of PBL-social model on creative thinking skills of pre-service physics teachers - Irwandani, Irwandani; Susilowati, Nur Endah; Soeharto, Soeharto (Education and Development Research, 2025)
This study examines the effectiveness of the Socio-Based Problem-Based Learning (PBL-Socio) model in enhancing the creative thinking skills of prospective physics teachers. Rooted in constructivist pedagogy, the PBL-Socio model integrates real-world social issues into the learning process to foster deeper engagement and higher-order thinking. A quasi-experimental design was conducted involving 53 undergraduate students from a physics education program in Indonesia, divided into experimental and control groups. The experimental group engaged in PBL-Socio activities, while the control group followed conventional instruction. Students’ creative thinking abilities—measured through fluency, flexibility, and originality—were assessed using an open-ended instrument and analyzed with the Rasch measurement model. Results showed a notable improvement in the experimental group’s creative thinking performance, with a mean gain of +1.63 logits compared to +1.03 in the control group. Rasch analysis indicated more consistent performance, reduced score variability, and stronger alignment with high-difficulty items among students exposed to the PBL-Socio model. Further analysis through Differential Item Functioning (DIF) revealed meaningful differences across learning styles and educational backgrounds, emphasizing the importance of inclusive instructional design. The findings suggest that integrating socially relevant content into physics instruction can significantly enhance both the quality and equity of creative thinking development in teacher education. This study contributes to the growing body of evidence supporting socially contextualized learning as a powerful driver of 21st-century competencies in STEM education.